2018
DOI: 10.1111/ceo.13198
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term visual outcomes for treatment of submacular haemorrhage secondary to polypoidal choroidal vasculopathy

Abstract: IVB monotherapy appears to be as effective as combination therapies for treating SMH secondary to PCV with regards to BCVA at 24 months, and may be a cost-effective strategy for long-term management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Kang et al compared three treatment methods for SMHs secondary to PCV including intravitreal anti-VEGF monotherapy, pneumatic displacement with anti-VEGF therapy, and pars plana vitrectomy with anti-VEGF therapy, and found little difference in the VAs at 2 years among the three treatments. 12 In the current study, multiple regression analyses showed that neither pneumatic displacement nor anti-VEGF therapy after the development of large SMHs significantly affected the BCVA 1 year later; however, these results may be attributable to the small sample sizes.…”
Section: Discussioncontrasting
confidence: 67%
“…Kang et al compared three treatment methods for SMHs secondary to PCV including intravitreal anti-VEGF monotherapy, pneumatic displacement with anti-VEGF therapy, and pars plana vitrectomy with anti-VEGF therapy, and found little difference in the VAs at 2 years among the three treatments. 12 In the current study, multiple regression analyses showed that neither pneumatic displacement nor anti-VEGF therapy after the development of large SMHs significantly affected the BCVA 1 year later; however, these results may be attributable to the small sample sizes.…”
Section: Discussioncontrasting
confidence: 67%
“…Overall, at 2 years post‐intervention there was no reported sustained overall difference in BCVA between the three groups . Despite small numbers ( N = 10) the potential for significant visual improvement (three line gain or more) may be more likely with pneumatic displacement.…”
mentioning
confidence: 88%
“…In this issue, Kang et al . report a retrospective review of 48 consecutive Korean eyes diagnosed with significant submacular haemorrhage involving the fovea centre secondary to PCV, and describe their outcomes when allocated one of three treatment arms: intravitreal bevacizumab (IVB) alone, IVB with pars plana vitrectomy (PPV) or IVB with pneumatic displacement (PD) . Pathways were allocated by the treating specialist and despite the largest group of those undergoing IVB monotherapy, baseline VA suggest that those with worse vision were significantly more likely to undergo PPV.…”
mentioning
confidence: 99%
“…Intravitreal administration of anti-VEGF is one of the effective treatment modalities for submacular hemorrhage secondary to PCV [14,15]. Studies have reported anatomical and functional improvements in both the as-needed regimen [14,16,17] as well as the fixed-dose regimen [15]. It is difficult to anticipate the complete cure of PCV; therefore, long-term treatment is usually required to preserve vision [18].…”
Section: Introductionmentioning
confidence: 99%